EMOTIONAL EFFECTS OF TOOTH LOSS IN PARTIALLY DENTATE PATIENTS PRESENTING AT TERTIARY CARE HOSPITAL OF ISLAMABAD - Rida Anjum; Sunia Gul; Muhammad Aamir Ghafoor Chaudhary; Hira Riaz (Pakistan Oral & Dental Journal, 2020)
The aim was to find out the emotional effects of tooth loss in partially dentate patients presenting to the Department of Prosthodontics at Islamic International Dental Hospital, Islamabad. It was a cross-sectional study. A questionnaire was filled by 100 partially dentate patients. Data was analyzed using SPSS version 13. The study showed that thirty nine percent (39%) of the patients were relieved after tooth loss. Fifty five percent (55%) of patients had no difficulty in accepting tooth loss. Sixty eight percent (68%) of all patients felt sad after losing their teeth. Fifty eight percent (58%) lost their anterior teeth in which fifty nine percent (59%) felt embarrassed in discussing their tooth loss (P value=0.025). Thirty two percent (32%) of patients felt less confident. These patients also had difficulty in accepting tooth loss (P value=0.000). Forty two percent (42%) of patients was unprepared for the emotional effects of tooth loss. Tooth loss affected emotions as most of our patients were prepared for the tooth loss but still they had difficulty in accepting tooth loss. They felt sad and handicapped. Patients were also not relieved after their tooth loss.